PERBUATAN MELAWAN HUKUM YANG DILAKUKAN OLEH ANAK DI BAWAH UMUR BERDASARKAN KETENTUAN PASAL 1367 KUH PERDATA STUDI DI POLSEK TENGGARONG KUTAI KARTANEGARA - Afhin Windriadi (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTAFHIN WINDRIADI, Faculty of Law, University of August 17, 1945 Samarinda. Unlawful acts undertaken by the Child Under the age of the provisions of Article 1367 KUH Perdata.Studi in police Tenggarong aquatic mammal.  This study aims to determine the definition of negligence that resulted in the death of another person and responsibility Parents of children who commit negligence in accordance with the provisions of Article 1367 of the Civil Code in police Tenggarong aquatic mammal.The research was conducted in August. Police Tenggarong in Kutai. This study merupkan kind of descriptive research analyst and also includes normative and empirical research. The type of data used is the data type Primary sourced from the Code of Civil (Civil Code), Act No. 35 of 2014.Based on the results, then be able to determine negligence committed by children and responsibility Parents of children who commit negligence that caused the death of a person under the provisions of Article 1367 of the Civil Code.